Program Corporate Social Responsibility Perbankan Syariah Di Bidang Pengolahan Ikan Sebagai Alternatif Pemberdayaan Umkm Jangka Panjang - Amimah Oktarina (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2016)
The growth of Islamic banking in Indonesia increasingly show the seriousness of the financial institutions in providing services to the community. However, the Islamic banking program of CSR does not aware yet the field of fish processing. Currently, Indonesian government began intense to empower the processed fish for the benefit of society. In Yogyakarta, the government is conducting “Gemarikan” to increase public interest in fish consumption. Based on these opportunities, the Islamic banking CSR program is directed to provide capital for SMEs conducting production activities in the field of fish processing.